2021
DOI: 10.1152/ajplung.00370.2020
|View full text |Cite
|
Sign up to set email alerts
|

E-cigarettes and health risks: more to the flavor than just the name

Abstract: Rationale: The growing interest in regulating flavoured E-liquids must incorporate understanding of the "flavouring profile" of each E-liquid - which flavourants (flavouring chemicals) are present and at what concentrations not just focussing on the flavour on the label. Methods: We investigated the flavouring profile of 10 different flavoured E-liquids. We assessed bronchial epithelial cell viability and apoptosis, phagocytosis of bacteria and apoptotic cells by macrophages after exposure to E-cigarette vapou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 91 publications
1
30
0
2
Order By: Relevance
“…Notably, this cellular and molecular damage known to drive tumorigenesis was independent of nicotine. Since that publication in 2016, several groups have identified further DNA damaging and DNArepair limiting effects of e-cigarettes, [30][31][32] as well as direct cytotoxic 30,[33][34][35][36] and carcinogenic 31,37 effects of e-cigarettes.…”
Section: Cytotoxic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this cellular and molecular damage known to drive tumorigenesis was independent of nicotine. Since that publication in 2016, several groups have identified further DNA damaging and DNArepair limiting effects of e-cigarettes, [30][31][32] as well as direct cytotoxic 30,[33][34][35][36] and carcinogenic 31,37 effects of e-cigarettes.…”
Section: Cytotoxic Effectsmentioning
confidence: 99%
“…Human alveolar macrophages and murine bone marrowederived macrophages exposed to e-cigarette aerosols have decreased phagocytosis and efferocytosis. 33,53 Human macrophages differentiated from the monocytic THP-1 cell line exposed to multiple common components of e-liquids (nicotine, propylene glycol, glycerol, and numerous flavorants) show diminished phagocytosis of bacteria after nicotine or flavor exposure, and diminished inflammatory cytokine secretion after exposure to any e-liquid component, including flavors. 54 Neutrophils from the circulation of e-cigarette aerosols as well as those exposed to e-cigarette aerosol extracts were found to have altered neutrophil extracellular trap formation and diminished antimicrobial function.…”
Section: Cellular Immunomodulationmentioning
confidence: 99%
“…Interestingly, the authors found that EC can alter bronchial epithelial cell cytokine secretion pathways in a flavor-dependent manner (45). In a more recent study, the flavoring profile of E-liquids has been found to cause bronchial epithelial cell apoptosis, alveolar macrophage phagocytic dysfunction, and to alter airway cytokines, pointing out the issue of regulating flavored E-liquids and the need of more rigorous studies providing clear data on the health impacts of flavored ECs (46). With particular regard to E-liquids mediated effects, two recent studies reported inappropriate activation Ca 2+ signaling pathways which in turn can have a detrimental impact on cell function and survival resulting in a loss of airway epithelial cell viability, and also in inducing pro-inflammatory responses and apoptosis (47,48).…”
Section: Staudt Et Al (50)mentioning
confidence: 99%
“…Although marketed as a healthier alternative to traditional cigarettes, 7 e‐cigarettes are not harmless and there are significant health risks associated with their use 8–10 . Short‐term consequences of use include inflammation of lung endothelial cells, airway irritations, oxidative stress and increased heart rate 11–16 . Studies examining long‐term health consequences have linked e‐cigarette use with cell death and increased risk of cardiovascular disease and cancer 17–19 …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Short-term consequences of use include inflammation of lung endothelial cells, airway irritations, oxidative stress and increased heart rate. [11][12][13][14][15][16] Studies examining long-term health consequences have linked e-cigarette use with cell death and increased risk of cardiovascular disease and cancer. [17][18][19] Australia has some of the most restrictive laws on nicotinecontaining e-cigarettes globally, with the manufacture, sale, or supply of such e-cigarettes without lawful authority prohibited in all Australian states and territories.…”
Section: Introductionmentioning
confidence: 99%